“I” Value Freedom, but “We” Value Relationships: Self-Construal Priming Mirrors Cultural Differences in Judgment - Gardner, Wendi L.; Gabriel, Shira; Lee, Angela Y. (Psychological Science, 1999)
The distinction between relatively independent versus interdependent self-construals has been strongly associated with several important cultural differences in social behavior. The current studies examined the causal role of self-construal by investigating whether priming independent or interdependent self-construals within a culture could result in differences in psychological worldview that mirror those traditionally found between cultures. In Experiment 1, European-American participants primed with interdependence displayed shifts toward more collectivist social values and judgments that were mediated by corresponding shifts in self-construal. In Experiment 2, this effect was extended by priming students from the United States and Hong Kong with primes that were consistent and inconsistent with their predominant cultural worldview. Students who received the inconsistent primes were more strongly affected than those who received the consistent primes, and thus shifted self-construal, and corresponding values, to a greater degree.